2008
DOI: 10.1002/syn.20556
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of carbamazepine and oxcarbazepine on excitatory synaptic transmission in rat hippocampus

Abstract: In this study, we have compared the effects of two structurally related compounds carbamazepine (CBZ) and oxcarbazepine (OXC), both in current use for the treatment of epilepsy and bipolar disorder, on fast excitatory transmission in rat hippocampal slices. Using electrophysiological recordings, we have investigated the effects of CBZ and OXC on repetitive action potential discharge of CA1 pyramidal neurons demonstrating that both compounds produced firing inhibition with similar IC(50) values. Moreover, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…; Giustizieri et al. ) which are higher compared to the concentration of CBZ used in our study. Moreover, our observation that application of 100 μ mol/L CBZ reduced the amplitude of the evoked response in slices from pharmacoresistant patients is confirmed by the results of Jandova et al.…”
Section: Discussioncontrasting
confidence: 55%
“…; Giustizieri et al. ) which are higher compared to the concentration of CBZ used in our study. Moreover, our observation that application of 100 μ mol/L CBZ reduced the amplitude of the evoked response in slices from pharmacoresistant patients is confirmed by the results of Jandova et al.…”
Section: Discussioncontrasting
confidence: 55%
“…Acute administration of CGS21680 did not affect AdA- or AMPA-evoked L-glutamate release, whereas acute CBZ administration reduced both AdA- or AMPA-evoked L-glutamate release. Therefore, acutely inhibitory effects of CBZ on astroglial L-glutamate release are probably not modulated by A2AR associated mechanisms [17,63]. Furthermore, under the condition of glutamate transporter function, acute CBZ administration did not affect basal astroglial L-glutamate release, whereas under the glutamate transporter blockade, acute CBZ administration increased basal astroglial L-glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that lacosamide, a voltage-gated sodium channel related AED, exerted neuroprotective effects against transient cerebral ischemic damage in gerbils [22]. In addition, it has been reported that OXC shows neuroprotective effect in an in vitro model of ischemia [23]. However, the effects of OXC in an in vivo model of ischemia are unclear.…”
Section: Introductionmentioning
confidence: 99%